A CONCEPTUAL FRAMEWORK FOR EVALUATING THE EFFECTIVENESS OF ROBOTIC GAME APPROACHES TO MOTIVATION AND PERFORMANCE IN GEOGRAPHY - Mohamad Amran Bin Manining; Soon Singh A/L Bikar Singh; Laila Meiliyandrie Indah Wardani (Universitas Mercu Buana Jakarta, 2022)
A conceptual framework for evaluating the effectiveness of robotic game approaches to motivation and performance in geography. In 2017, the standard secondary school curriculum (KSSM) replacing the previous curriculum was introduced as a continuation of curriculum changes in the 21st century. However, these changes still make Geography a compulsory subject for middle and upper secondary subjects. As a result of this change, fewer schools in Malaysia offer geography in the upper middle class and if so, the choice is given to middle school students. This situation is especially critical as most Geography teachers still practice conventional teaching methods in the classroom. The implication is that students are less motivated to study Geography and this phenomenon has also influenced their geographical achievement. Therefore, various 21st century teaching methods have been introduced in classroom learning and facilitating activities. One of the things that started to catch the attention of teachers was the game method. This is because the use of the game approach as a teaching tool has a positive impact on students' engagement and motivation to learn geography. However, unlike in Malaysia, the game's approach has been less widely introduced, especially in geography learning and facilitation in secondary schools. This is due to the lack of appropriate resources and the ability of teachers to apply the skills in learning and facilitating. Therefore, this conceptual framework was developed to evaluate the effectiveness of using a robotic game approach in improving student motivation and achievement in secondary school.